Evaluation of the safe use and dietary risk of beta-cypermethrin, pyriproxyfen, avermectin, diflubenzuron and chlorothalonil in button mushroom - Pengqiang Du (Nature Portfolio, 2017)
Abstract In this study, the residues of beta-cypermethrin, pyriproxyfen, avermectin, diflubenzuron and chlorothalonil in button mushrooms were investigated. The dietary risks of ingesting button mushrooms that have had these pesticides applied by two different methods under normal plant conditions were evaluated. The dissipation of these pesticides into the soil was also studied. According to the maximum residue limits (MRLs) and acceptable daily intakes (ADIs), the final residues of beta-cypermethrin, pyriproxyfen, avermectin, diflubenzuron, and chlorothalonil were safe for human consumption after these pesticides were applied by spraying 2 times at the dosages of 900, 750, 540, 562.5, and 540 g a.i.ha−1. The dissipation experiment results demonstrated that these pesticides dissipated rapidly after spraying, and there were no residues that could be detected at harvest time when the pesticides were mixed with substrates. According to this work, the application methods of spraying and incorporation with these pesticides at 1 and 1.5 times of the recommended dosage are safe and proper in cultivating button mushrooms.